A comprehensive evaluation of differentially expressed mRNAs and lncRNAs in cystitis glandularis with gene ontology, KEGG pathway, and ceRNA network analysis - Li, Chao (Transl Androl Urol, 2020)
BACKGROUND: Cystitis glandularis (CG) is a proliferative disorder of the urinary bladder characterized by transitional cells that have undergone glandular metaplasia. The underlying mechanism associated with this transformation is poorly understood. METHODS: The expression of messenger RNA (mRNA) and long non-coding RNA (lncRNA) from normal bladder mucosa and CG were compared using microarray analysis. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis was used to describe molecular interactions. RESULTS: Microarray analysis identified 809 significantly dysregulated mRNAs in CG tissues; 606 were up-regulated and 203 were down-regulated (greater than 2-fold difference in expression from normal tissue, P<0.05). KEGG pathway analysis showed that the mRNAs that co-expressed with lncRNAs were enriched in the cell cycle regulation pathway. Four up-regulated lncRNAs (ENST00000596379, ENST00000463397, NR_001446 and NR_015395) were identified in the coding-non-coding co-expression (CNC) network analysis as being associated with the expression of four mRNAs (SMAD3, ORC1, CCNA2 and CCNB2). NR_015395 was revealed to be a competing endogenous RNA (ceRNA) of miR-133a-3p that targets SMAD3. CONCLUSIONS: This is the first work to measure the expression of dysregulated lncRNA and ceRNA in CG and identify the crosstalk between mRNA and lncRNA expression patterns in the pathogenesis of CG.